OPPORTUNITIES FOR INCLUSIVE MUSIC EDUCATION IN THE GENERAL EDUCATION SCHOOL: AN ANALYSIS OF TEACHERS’ ATTITUDES - STRAKŠIENĖ, Diana (Studia Universitatis Babes-Bolyai Musica, 2020)
The article presents a qualitative study aimed at revealing the attitude of music educators towards inclusive education opportunities in the general education school. A relatively positive attitude of teachers towards the meaning and purpose of inclusive education has been identified: most music teachers perceive the meaning and purpose of inclusive education as an aspiration, naming the following key principles of inclusive education: accessibility of education, creation of equal opportunities for every learner, a supportive educational atmosphere, positive relationships with pupils and colleagues and the like. On the other hand, it has been found that up until now, for some teachers, the conception of inclusive education is not fully clear: inclusive education is still perceived as a method that helps to serve children who have disabilities in general educational settings. Research data revealed that educators’ attitudes towards inclusive education depended on age: older teachers were not only more sceptical than younger, assessing the idea of inclusive education itself, but also avoided collaboration and sharing good practice with colleagues in the educational process.